Hansesmarkite, Ca2Mn2Nb6O19·20H2O, a new hexaniobate from a syenite pegmatite in the Larvik Plutonic Complex, southern Norway. (1st May 2017) - Friis, H.; Weller, M. T.; Kampf, A. R.
The new mineral hansesmarkite (IMA2015-067), Ca2Mn2Nb6O19·20H2O, was discovered at the AS Granit larvikite quarry in Tvedalen, Larvik, Vestfold, Norway. Hansesmarkite forms faintly yellow crystals up to 0.3 mm or thin coatings in patches on gonnardite. Hansesmarkite is biaxial (+) with refractive indices (white light): α = 1.683(2), β = 1.698(2) and γ = 1.745(3); 2V(meas.) = 60.7(6)° and 2V(calc.) = 60.3°. The mineral exhibits moderate dispersion (r > v) and is pleochroic with X (almost colourless) < Y ( pale yellow) << Z (orangey yellow). The optical orientation is X ^ c = 20°, Y ^ b = 16° and Z ^ a = 5°. The empirical formula based on five electron probe microanalyses and calculated based on Nb = 6 apfu is (Ca1.93Na0.02K0.01) ∑1.96(Mn1.79Fe0.11)∑1.90Nb6O18.84·20H2O, with H2O determined from the structure solution. The mineral is triclinic, P1, with a = 9.081(4), b = 9.982(8), c = 10.60(1) Å, α = 111.07(8), β = 101.15(6), γ = 99.39(5)°, V = 850.8(13) Å3 and Z = 1. The structure was solved at 120 K because of thermal instability of the mineral and refined to R1 = 2.50% for Fo > 4σ. The strongest reflections in the x-ray diffraction diagram are: [dobs. in Å (I)(hkl)] 9.282(36)(001), 8.610(100)(100, 011), 3.257(30)(031, 131) and 3.058(18)(130, 212). Hansesmarkite is the third naturally occurring hexaniobate in which six edge-sharing Nb-octahedra form the Lindqvist ion. These are linked via Mn-octahedra forming rods along [100] and Ca is located between the rods, creating a three dimensional structure via hydrogen bonds.